O Cursinho Popular dos Alunos da PUC-SP – Valdemar Gomes como espaço de resistência e formação: (1997 – 2006) - Souza, Henrique Antonio Profili de (2024)
This study’s objective is to investigae the history of the Cursinho Popular dos Alunos da PUC-SP. This reseach belongs to the study line “Brazilian education: production, circulation and cultural apropriation” that belongs to the resarch group “History of Institutions and Intelectuals of Brazilian Education”, inside the post graduation program Education: History, Politics, Society (EHPS). That way, the study try to situate the Cursinho among the Other prep courses that existed at the Catholic University of São Paulo (PUC-SP). The initial hypotesis is that this school institution was constituted as a space of political formation for teachers and students and a place that has developed its own school culture. As research sources this research used printed documents and interviews with teachers and founders that worked at the prep course from 1997 to 2006. Based in Oral History and Memory, the research uses authors as Alberti (1996), Pollack (1992); School Culture: Julia (1995) and Benito (2017); Popular preparatory course: (Castro) (2019), Zago (2008)